Assessing the hidden dangers of volcanic CO2 exposure: a critical review of health impacts - Boada, Luis D.; Simbaña-Rivera, Katherine; Rodríguez-Pérez, C.; Fuentes-Ferrer, M.; Henríquez-Hernández, Luis Alberto; López-Villarrubia, E.; Alvarez-León, E. E. (Frontiers in Public Health, 2024)
Volcanic eruptions pose significant health risks to inhabitants of affected regions, with volcanic gases, including carbon dioxide (CO2), being a notable concern. This review examines the implications of long-term exposure to volcanic CO2 emissions on public health, highlighting the shift in understanding from acute to chronic health effects. Recent studies have underscored the need to reevaluate the adverse health impacts of CO2 beyond acute toxicity symptoms. While previous guidelines deemed an indoor (residential) acceptable long-term exposure range (ALTER) of ≤ 3,000 parts per million (ppm) in residential housing areas, emerging evidence suggests that even concentrations within the range of 3,000 to 1,000 ppm may induce deleterious health effects. International agencies now advocate for lower safe indoor CO2 levels (600-1,000 ppm), necessitating a reassessment of public health strategies in volcanic areas. This review argues for increased awareness among local and public health authorities about the chronic toxicity of CO2 exposure and emphasizes the importance of safeguarding populations from the adverse health effects induced by CO2 exposure.